The Influence of Bank Specific Factors on Financial Stability in Sharia Commercial Banks in Indonesia from 2013 to 2023 - Kusnaedy , Nirmala Putri; Setiawan; Qolbi, Satria Kharimul; Abdusyakur , Muhammad Zulfan (Indonesian Journal of Economics and Management, 2025)
This study examines the effect of bank-specific factors on the financial stability of Sharia Commercial Banks in Indonesia from 2013 to 2023. Using a quantitative approach and panel data regression analysis on secondary data from 15 Islamic banks listed on the IDX, the study finds that Non-Performing Finance (NPF) has a significant negative effect, Bank Size has a significant positive effect, and Bank Age has a positive but insignificant effect on financial stability. Collectively, NPF, Bank Size, and Bank Age significantly influence financial stability.